The Political Economy of Assisted Immigration: Australia 1860-1913 - Timothy J. Hatton (Institute of Labor Economics (IZA), 2023)
From 1860 to 1913 the six colonies that became states of Australia strove to attract migrants from the UK with a variety of assisted passages. The colonies/states shared a common culture and sought migrants from a common source, the UK, but set policy independently of each other. This experience provides a unique opportunity to examine the formation of assisted immigration policies. Using a panel of colonies/states over the years 1862 to 1913 I investigate the association between measures of policy activism and a range of economic and political variables. Assisted migration policies were positively linked with government budget surpluses and local economic prosperity. They were also associated with political participation including the widening of the franchise and remuneration of members of parliament. While the reduction in travel time to Australia reduced the need for assisted migration, slumps in the UK increased the take-up of assisted passages.
Keywords: F22; N37; N47; 330; colonial Australia; assisted passages; international migration